Lending for Jobs Operations - Robalino, David; Tokle, Siv (World Bank, Washington, DC, 2017)
This paper develops a general framework to inform the design of a new generation of jobs lending operations. The paper discusses the rationale for developing jobs focused lending operations with specific targets in terms of job creation, job quality, and labor markets outcomes for vulnerable population groups. It reviews the current portfolio of jobs-flagged lending operations, discusses the limitations of existing interventions, and outlines options to optimize countries lending portfolios and develop new, integrated, jobs lending operations on the basis of jobs diagnostics and jobs strategies. The paper provides examples of innovative projects that are currently under preparation or implementation, including jobs investment projects that link supply-side and demand side interventions; jobs Program for Results (PforRs), and jobs Development Policy Lending. The final section describes the types of monitoring and evaluation systems that these new projects would require to track jobs outcomes.